Analisis Akuntabilitas dan Transparansi Dana Masjid Terhadap Laporan Keuangan Masjid Jami’ Al Ridha Lima Puluh Kabupaten Batu Bara - Amelia, Afni; Ardhansyah Putra Hrp; Sri Fitria Jayusman (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2025)
The purpose of this study is to determine the extent of the level of accountability of financial reports at the Jami' Al-Ridha Mosque. To determine the application of transparency of the financial reports of the Jami' Al-Ridha Mosque to the congregation and other related parties. To determine whether the financial report of the Jami Al-Ridha Lima Puluh Mosque has presented financial information in an accountable and transparent manner. This type of research is qualitative data. The subjects in this study were BKM (Mosque Prosperity Agency), in this case the chairman, secretary, and treasurer who can provide representative information and have access and influence over all operational activities of the Jami' Al-Ridha Mosque. This study uses the Jami' Al-Ridha Mosque, Lima Puluh District, Batu Bara Regency as the object of research. The results of this study are that the Jami' Al-Ridha Lima Puluh Mosque, Batu Bara Regency is considered not to have presented adequate financial reports and in accordance with the provisions of ISAK No. 35. The Jami' Al-Ridha Lima Puluh Mosque only presents financial reports in the form of cash inflow and cash outflow reports, while the financial position report (balance sheet), activity report, cash flow report, and notes to the financial report have not been presented, this is due to the lack of human resources management regarding finances. The implementation of transparency in financial management at the Jami' Al-Ridha Lima Puluh Mosque, Batu Bara Regency is considered transparent in principle, but still very simple. Accountability for financial management at the Jami' Al-Ridha Lima Puluh Mosque, Batu Bara Regency, although still simple, but the governance is very sharia, implementing the principles of trust and truth in it.